Systemic design and policy making: The case of the Retrace project - Barbero, Silvia; Pallaro, Agnese (FormAkademisk, 2018)
The paradigm shift from a linear to a circular economic model has been increasingly advocated by many, from the scientific community to governments. The benefits of a Circular Economy (CE) are particularly appealing for Europe, considering the issues Europe is currently facing. Even though the European Union (EU) promotes activities to support the transition to a CE, several economic, social and regulatory barriers hinder this. The full potential of a CE can be realised only after these barriers have been overcome. Given the current European context in relation to policymaking for a CE, the paper provides a case study of the RETRACE Interreg Europe project to argue that the methodology of the Systemic Design approach can support the transition to a Circular Economy, thus overcoming existing barriers. The focus of the discussion will be narrowed to the Piedmont region (Italy) to better support the argument.